Proceedings of the 50th Annual ACM SIGACT Symposium on Theory of Computing 2018
DOI: 10.1145/3188745.3188850
|View full text |Cite
|
Sign up to set email alerts
|

The Gram-Schmidt walk: a cure for the Banaszczyk blues

Abstract: An important result in discrepancy due to Banaszczyk states that for any set of n vectors in R m of ℓ 2 norm at most 1 and any convex body K in R m of Gaussian measure at least half, there exists a ±1 combination of these vectors which lies in 5K. This result implies the best known bounds for several problems in discrepancy. Banaszczyk's proof of this result is non-constructive and a major open problem has been to give an efficient algorithm to find such a ±1 combination of the vectors.In this paper, we resolv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
60
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(61 citation statements)
references
References 36 publications
(42 reference statements)
1
60
0
Order By: Relevance
“…We will apply these properties shortly. A recent result by Matousek et al [33] shows the following property about connecting discrepancy to γ 2 , which was recently made constructive in polynomial time [5]. Let the size of S be m = O(n O(d) ), and define an m × n matrix G so its rows are indexed by x ∈ S and columns indexed by p ∈ P , and G x,p = K(p, x).…”
Section: Upper Bound For Kde Coresetmentioning
confidence: 99%
“…We will apply these properties shortly. A recent result by Matousek et al [33] shows the following property about connecting discrepancy to γ 2 , which was recently made constructive in polynomial time [5]. Let the size of S be m = O(n O(d) ), and define an m × n matrix G so its rows are indexed by x ∈ S and columns indexed by p ∈ P , and G x,p = K(p, x).…”
Section: Upper Bound For Kde Coresetmentioning
confidence: 99%
“…Plugging back into (17), we get E[e λy (Xτ −x) ] ≤ e τ λ 2 ε 2 0 n 2 /ε 1 . The standard exponential moment argument then implies (16).…”
Section: We Finish This Section With the Proof Of Lemma 13mentioning
confidence: 97%
“…Despite this success, Banaszczyk's more recent results on signed series [3], and the last author's upper bounds on the discrepancy of axis-aligned boxes [27], both proved using the techniques used in [2], remain out of reach algorithmically. Extending the techniques of this paper and of [6] to give constructive proofs of these results is an interesting open problem.…”
Section: Conclusion and Follow-up Workmentioning
confidence: 97%
“…Subsequently to the publication of an extended abstract of this paper [14], the first three named authors, jointly with Bansal, showed the existence of a polynomial-time sampling algorithm for an O(1)-subgaussian distribution on signed sums of vectors with 2 norm at most 1 [6]. Together with the results in this paper (specifically Corollary 6.6), this sampling algorithm implies a new constructive proof of Banaszczyk's theorem in its full generality.…”
Section: Conclusion and Follow-up Workmentioning
confidence: 99%